2020
DOI: 10.3390/atmos11090910
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of the Boundary Layer Height and of the Wind Field over Greece

Abstract: In this study, a climatology of two key boundary layer features, the Planetary Boundary Layer Height (PBLH) and the wind field over Greece is derived. The climatology is based on daily soundings collected in Athens, Thessaloniki and Heraklion and spanning a 32-year period. The PBLH is estimated using a method based on the gradient of potential temperature and a method based on the bulk Richardson number. The wind field is analyzed by calculating the wind shear and the turning angle of the wind vector between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…There are many methods to diagnose the PBLH, and the commonly used methods include the potential temperature gradient method [2,35], parcel method [36,37], relative humidity gradient method [21], specific humidity gradient method [21], refractive index gradient method [35,38], and Richardson number method [20,31]. Seidel et al [9,20] compared and evaluated different diagnostic methods and confirmed that the Richardson number method is more suitable for the diagnosis of the PBLH in large-volume datasets, and this method is suitable for both the stable boundary layer (SBL) and convective boundary layer (CBL).…”
Section: Pblh Diagnosis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many methods to diagnose the PBLH, and the commonly used methods include the potential temperature gradient method [2,35], parcel method [36,37], relative humidity gradient method [21], specific humidity gradient method [21], refractive index gradient method [35,38], and Richardson number method [20,31]. Seidel et al [9,20] compared and evaluated different diagnostic methods and confirmed that the Richardson number method is more suitable for the diagnosis of the PBLH in large-volume datasets, and this method is suitable for both the stable boundary layer (SBL) and convective boundary layer (CBL).…”
Section: Pblh Diagnosis Methodsmentioning
confidence: 99%
“…The Earth's surface exchanges heat, momentum, water vapor, and chemicals with the free atmosphere through the PBL. Since the PBL involves many processes, such as convective activity, turbulent mixing, low-layer cloud formation, pollutant diffusion, and surface energy budget, the PBL plays a key role in many aspects, such as weather, climate, and air pollution [2]. The planetary boundary layer height (PBLH) is an important parameter for characterizing the structural characteristics of the PBL.…”
Section: Introductionmentioning
confidence: 99%
“…The profiles of θ are used to derive the atmospheric BLH from dropsonde measurements and reanalyses. The BLH is defined here as the altitude where the largest vertical gradient in θ is found (similar to Seidel et al, 2010;Dai et al, 2014;Bakas et al, 2020;Sinclair et al, 2022). For estimating the cloud top heights (CTHs), the 532 nm backscatter ratio from the water vapor differential absorption (WALES) lidar is used (Wirth et al, 2009).…”
Section: Airborne Observationsmentioning
confidence: 99%
“…The transfer coefficients of heat and humidity are directly calculated using the most recent COARE 3.5 bulk air-sea algorithm (Edson et al, 2013;Bariteau et al, 2021). At winds speeds up to 20 m s −1 , COARE has a reported uncertainty of around 10 % (Fairall et al, 2003;Edson et al, 2013).…”
Section: Airborne Observationsmentioning
confidence: 99%
See 1 more Smart Citation